Possible hepatocellular toxicity of EGCG under the influence of an inflammagen - Saleh, Ibrahim G; Ali, Zulfiqar; Abe, Naohito; Hamada, Farid M; Abd-Ellah, Mohamed F; Walker, Larry A; Khan, Ikhlas A; Ashfaq, Mohammad K (Journal of Applied Biomedicine, 2014)
Epigallocatechin-3-gallate (EGCG) is widely used as a weight controlling supplement. Concerns about its safety evoked after cases of hepatotoxicity occurred upon its use. The underlying factors that could be involved in EGCG associated hepatotoxicity are not fully studied. In this study, we investigated the possible impact of lipopolysaccharide (LPS), as an inflammagen, on the effect of EGCG on hepatocytes. HepG2 cells were treated with different concentrations of EGCG (100, 200, 500 μM), with and without LPS (10 nM)-presensitization of the cells. Viability of HepG2 cells decreased with the increased concentrations of EGCG; the viability was even lesser in LPS-presensitized cells. Oxidative stress (Ox.LDL and CXCL16), the expression of nuclear retinoic receptors (RAR, RXR) and the biomarkers of hepatocellular injury (TNFα, TGFβ1) were all relatively higher in LPS-presensitized cells compared to non-sensitized cells upon treatment with EGCG. Sensitization of HepG2 cells with LPS alone did not affect the viability or any of the other biomarkers considered in this study. In conclusion, EGCG alone can be harmful to liver at high concentrations and this effect may become more pronounced under the influence of an inflammagen.
Keywords: hepatocyty; Polyphenols; In Vitro Techniques; Hepatocytes; polyfenoly; Inflammation; Catechin; Hep G2 Cells; techniky in vitro; zánět; Cell Survival; viabilita buněk; buňky Hep G2; epigallocatechin-3-gallate (EGCG); katechin